Effects of intramuscular alfaxalone and dexmedetomidine alone and combined on ocular, electroretinographic, and cardiorespiratory parameters in normal cats - Guo, Yizhe; Mao, Sichao; Zhou, Zhenlei (Frontiers in Veterinary Science, 2024)
Background: This study aimed to determine the effects of intramuscular (IM) administration of alfaxalone with or without dexmedetomidine on short electroretinography (ERG), ocular parameters and cardiorespiratory in healthy cats. Methods: Eight healthy female spayed cats were treated with three sedation protocols: IM administration of 5 µg/kg dexmedetomidine (DEX), 5 mg/kg alfaxalone (ALF), and 5 µg/kg dexmedetomidine plus 5 mg/kg alfaxalone (DEX+ALF). The washout period after each treatment was 2 weeks. Physiological parameters, time metrics, intraocular pressure (IOP), Schirmer tear test 1 (STT-1) and a short ERG protocol were recorded. For age data, weight data, time metrics and ERG data, one-way ANOVA with Bonferroni posterior comparisons were performed. For physiological parameters, IOP and STT-1 data, two-way repeated measures ANOVA with Bonferroni posterior comparisons were performed. Statistical significance was set at a p-value < 0.05. Results: IOPs were increased in all three groups compared to baseline and showed no significant differences among three groups at any time point. STT -1 values were decreased significantly during the process. Significant differences were noticed between a-wave amplitude in the dark-adapted response between DEX and ALF, and a-wave amplitude in light-adapted response between ALF and DEX+ALF. Conclusions: This study demonstrates the feasibility of three sedation protocols for short ERG recording in cats. All these treatments resulted in increased IOP values and reduced STT-1 values. But baseline data of ERG was not obtained as a blank control in cats.